Health Education About Ergonomic Positions in an effort to Prevent Injuries at Work - Udin Rosidin; Iwan Shalahuddin (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Occupational health and safety (K3) is the main means of preventing work accidents. Apart from preventing accidents, K3 is also very important to ensure worker welfare, protect assets, and increase productivity. The implementation and application of occupational health are currently still not optimal as can be seen from the high number of work accidents. Based on the results of a survey by PPN 46 students in one of the garment home industries located in RW 021, Kota Wetan Subdistrict, data was found that the implementation of occupational health programs is currently still very lacking, marked by a lack of knowledge among home industry owners or workers regarding occupational health. Other data obtained showed that workers said they were used to lifting heavy loads on their shoulders compared to using tools, and all workers complained of musculoskeletal problems. The activity aims is to increase workers' knowledge in implementing ergonomic positions as an effort to prevent injuries at work. The activity stages start from problem identification, social preparation, and administrative preparation. Then it continues with the implementation and evaluation stages of activities. The results of the activity showed an increase in worker knowledge of 11.2 points. The average pretest score was 66.4 points and the average posttest score was 77.6 points. Activities ran smoothly according to the planned time. It is hoped that the health education activities that have been carried out can be continued periodically by the home industry owner and the Guntur Community Health Center.